Discovery of Pratylenchus zeae Causing Root Rot of Winter Wheat in Anhui Province of China - Gao, Lingling (Plant disease, 2025)
Root-lesion nematode (RLN), Pratylenchus zeae Graham, 1951, is a serious nematode pest in a number of agronomic and industrial crops (Liu et al. 2017). Wheat (Triticum aestivum) is one of the most important food crops in Anhui province of China. In May 2023, a survey was conducted for RLNs in winter wheat fields in Woyang county of Bozhou City, Anhui province, China. The samples were collected about 20 days before wheat (cv. Gushenmai 19) harvest. The plants were growing poorly, with distinct brown lesions on the wheat roots. The RLNs were extracted with the modified Baermann funnel apparatus (Hooper et al. 2005). The RLNs were found in eight collected samples, an average of 51 nematodes per gram of root and 128 nematodes per 100 cm3 of soil. The extracted RLNs were disinfected with 0.3% streptomycin sulfate and one individual female nematode were cultured on carrot disks at 25°C for propagation as described before (Wang et al. 2021). The RLNs species identification was based on morphological and molecular criteria. The main morphological measurements of adult females (n = 15) included body length = 490.5 μm (mean) ± 13.1 (standard deviation) (range = 471.3 to 523.1 μm), stylet length = 16.1 μm ± 0.7 (14.0 to 16.9 μm), tail length = 27.3 μm ± 5.3 (18.9 to 34.1 μm), a = 24.8 ± 1.8 (21.9 to 27.8), b = 5.2 ± 0.3 (4.5 to 5.9), c = 17.8 ± 1.9 (14.9 to 20.3), two annules on the lip region. No males were found in the specimens. The morphological characters of this population are consistent with P. zeae as described previously (Castillo and Vovlas, 2007). Furthermore, the individual female was used for the molecular identification, and the DNA was extracted as described previously (Wang et al. 2011). The primers of D2A/D3B (Subbotin et al. 2006) and TW81/AB28 (Vovlas et al. 2011) were used to amplify the rDNA 28S D2-D3 region and rDNA-ITS region, respectively. The PCR products were sequenced, the newly obtained sequences of the rDNA 28S D2-D3 region (782 bp) and rDNA-ITS region (669 bp) in this study were submitted to NCBI. The obtained 28S D2-D3 region sequence (GenBank Accession No. PQ859281 and PV083139) had 100% identity with P. zeae sequences available from GenBank (KY424256 and KY424263). The obtained ITS sequences in this study (PQ857687 and PV089700) had more than 98% identity with P. zeae sequences available from GenBank (OP456372 and OP466367). Both morphological and molecular data confirmed the presence of P. zeae. To validate the reproductive capacity of the RLNs on winter wheat, a greenhouse experiment was conducted at 25°C, following the modified Koch's postulates protocol. Wheat plants were grown in 8 pots, each with three plants (cv. Gushenmai 19) were inoculated with 1000 P. zeae and grown in 1.5-liter pots. Two months after inoculation, the wheat roots were washed and brown lesions were observed. RLNs in the soil and roots were extracted as previously described and the population was found to have increased substantially. The average of final number of nematodes/pot was about 1859 in soil and 793 in roots. The reproduction factors (final population/initial population) were greater than 1 (mean 2.65). Those results confirmed that this nematode population infects and reproduces well on this wheat cultivar. P. zeae has only been reported on winter wheat in Shanxi Province of China (Liu et al. 2007). To our knowledge, this is the first report of P. zeae infecting winter wheat in Anhui province of China. Since P. zeae can cause considerable damage to winter wheat, strategic measures should be taken to prevent the spread of P. zeae to other regions